Estilos de vida saludable y su relación con el rendimiento académico en estudiantes de contaduría - Marín Trujillo, Laura Daniela (Universidad Antonio Nariño, 2021)
The objective of this study is to determine the practices and beliefs of healthy lifestyles and their relationship with academic performance in Public Accounting students. A descriptive cross-sectional study was carried out. The population universe is made up of all Public Accounting students at the Antonio Nariño University. The sample size consisted of 83 students to whom the Practices and Beliefs About Life Styles questionnaire was applied, validated by Arrivillaga, Salazar and Gómez, which assesses six dimensions of lifestyle: condition, physical activity and sport; Leisure time; self-care and medical care; Feeding Habits; consumption of alcohol, tobacco and other drugs; and I dream.